Potassium iodide enhances the killing effect of methylene blue mediated photodynamic therapy against F. monophora - Qian Li; Yinghui Liu; Jinjin Zheng; Yangxia Chen; Zeyu Liu; Qiulin Xie; Dongmei Li; Liyan Xi; Judun Zheng; Hongfang Liu (Photodiagnosis and Photodynamic Therapy, 2024)
Background: Chromoblastomycosis (CMB) is a chronic granulomatous fungal infection that affect the skin and subcutaneous tissues. It is clinically problematic due to limited treatment options, low cure rates, and high rates of relapse. This underscores the necessity for innovative treatment approaches. In this study, potassium iodide (KI) combined with Methylene Blue (MB) mediated antimicrobial photodynamic therapy (PDT) were assessed in the treatment of Fonsecaea monophora (F. monophora) both in vitro and in vivo. And the underlying mechanism that contributes to the efficacy of this treatment approach was investigated. Methods: In vitro experiments were conducted using different combinations and concentrations of MB, KI, and 660 nm light (60 mW/cm2) to inhibit F. monophora. The study was carried out using colony-forming unit (CFU) counts and scanning electron microscopy (SEM). The production of singlet oxygen (1O2), free iodine (I2), hydrogen peroxide (H2O2), and superoxide anion during the KI combined MB-mediated antimicrobial PDT process was also detected. In vivo experiments were developed using a Balb/c mouse paw infection model with F. monophora and treated with PBS, 10 mM KI, 2 mM MB +100 J/cm² and 10 mM KI+2 mM MB +100 J/cm² respectively. Inflammatory swelling, fungal load and histopathological analyses of the mouse footpads were assessed. Results: KI enhanced the killing effect of MB-mediated antimicrobial PDT on the conidial spores of F. monophora at the cell and infected animal model level. During the process, the main antimicrobial agents in KI combined with MB- mediated antimicrobial PDT could produce stronger toxic active species including free I2 and H2O2. Conclusion: KI combined with MB-mediated antimicrobial PDT could be an effective adjunct therapy for treating CBM.